ACCELERATING GROWTH THROUGH THE IMPLEMENTA-TION OF ISLAMIC BANKING GOVERNANCE - Abubakar, Lastuti; Handayani, Tri (UI Scholars Hub, 2021)
Indonesian sharia banking industry’s growth chart shows a rising, albeit decelerating. Data published by the FSA indicates that Islamic banking accounted for 4.81% of market share to achieve the growth assets 11.97% as of June 2016. At the global level, the Islamic financial services sector including banking, control of 3% and together with Qatar, Saudi Arabia, Malaysia, United Arab Emirates and Turkey became the driving force of Islamic finance in the future. Based on the data above, efforts are needed to accelerate the growth of Islamic banking in both the national and global level to take advantage of opportunities that are still open. One of the strategic issues faced and the impact on the growth of national banks is understanding and awareness is still low, causing public misperception among others, relating to the terms, covenants and transparency of the product; as well as costly. The problem will be discussed is how the implementation of sharia governance can be used as a means to increase public confidence in the Islamic banking and ultimately encourage the growth of Islamic banking. Regulation on governance in Islamic banking mandated in Article 34 of Law No: 21 of 2008 concerning Islamic Banking which requires Islamic banks and Sharia implement good governance which include the principles of transparency, accountability, responsibility, professional and fairness in conducting its business activities with regard sharia principles in the form of a ban on business ac-tivities that contain elements of usury, maysir, gharar, zhulm, tabdzir, risywah and maksiyat. Besides Islamic bank based spiritual footing, which is committed to conducting business based on principles of halal and Tayib, so the function of Islamic banking can as an intermediary that is capable of pros-pering the people and sustainable. Therefore, Sharia Supervisory Board is obliged to ensure that banking activities comply with sharia and sharia governance principles.